2021
DOI: 10.3390/info12010034
|View full text |Cite
|
Sign up to set email alerts
|

An Advanced Abnormal Behavior Detection Engine Embedding Autoencoders for the Investigation of Financial Transactions

Abstract: Nowadays, (cyber)criminals demonstrate an ever-increasing resolve to exploit new technologies so as to achieve their unlawful purposes. Therefore, Law Enforcement Agencies (LEAs) should keep one step ahead by engaging tools and technology that address existing challenges and enhance policing and crime prevention practices. The framework presented in this paper combines algorithms and tools that are used to correlate different pieces of data leading to the discovery and recording of forensic evidence. The colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…The logical operators in Description Logic hold particular significance for their role in shaping the semantics of the ontology. Standard constructors include existential quantification (∃), universal quantification (∀), conjunction (∩), and negation (¬), among others [129][130][131][132]. These operators allow for the expression of intricate relationships and constraints among ontology elements.…”
Section: Description Logicmentioning
confidence: 99%
See 1 more Smart Citation
“…The logical operators in Description Logic hold particular significance for their role in shaping the semantics of the ontology. Standard constructors include existential quantification (∃), universal quantification (∀), conjunction (∩), and negation (¬), among others [129][130][131][132]. These operators allow for the expression of intricate relationships and constraints among ontology elements.…”
Section: Description Logicmentioning
confidence: 99%
“…This formalization using Description Logic provides a mathematical foundation for the ontology and enables the application of automated reasoning tools for ontology verification and query answering. Thus, the transition from tabular representations to Description Logic enhances the ontology's operational effectiveness and semantic clarity [132][133][134][135].…”
Section: Description Logicmentioning
confidence: 99%
“…Anomaly detection is used in several scientific domains such as healthcare, intrusion detection, sensor network, and fraud detection, to name a few. Detecting irregularities in the network, identifying anomalies in financial transactions, detecting fraudulent activities, and detecting anomalies in medical images are some anomaly detection applications [36]. In networks, anomaly patterns can be identified based on the classification of packet data containing abnormal patterns.…”
Section: Related Workmentioning
confidence: 99%
“…It is found that the random forest prediction effect has obvious advantages, and it is said that the random forest also plays an important role in gene prediction. Demestichas [27] predicted the remote sensing location by using the random forest model and other commonly used prediction algorithm models and found that the prediction accuracy of the random forest model is the highest. Kurniawan [28] simplified the financial indicators based on the correlation and importance of the indicators, constructed the financial early warning model, and established the variable precision weighted average roughness decision tree, which significantly improved the noise prevention ability and classification accuracy of the early warning model.…”
Section: Related Workmentioning
confidence: 99%